The last of the southern girls - Morris, Willie 1934-1999 (Knopf, 1973)
Carol Hollywell is beautiful, smart, elegant, and charming. A debutante from Arkansas, she is heir to a good Southern name and a small Southern fortune. She knows what she wants and, more important, knows how to get it. She is, in other words, the prototypical southern belle, a Scarlett O'Hara for the 1950s, and when she moves to Washington, D.C., in 1957, she sets the town on its ear. Willie Morris' clever novel (loosely based on a real-life figure) follows this headstrong woman from her arrival in the Capital and traces the ups and downs of her life in the political and social whirl of the city over the next decade and a half. Eventually, she becomes romantically involved with a prominent congressman, but the genuine satisfactions they find in their relationship cannot long withstand the pressures of the ambitions both of them harbor.--From publisher description.
Keywords: Washington (D.C.) -- Fiction